(untitled) (Texas Journal of Engineering and Technology, 2025)
This paper examines the physical processes accompanying the occurrence of an electric discharge in an aqueous medium, which is a key element of electrohydraulic technologies. Special attention is given to the mechanisms of discharge initiation, the influence of medium parameters (pressure and conductivity), and the characteristics of high-voltage pulses. The study aims to determine the optimal conditions for effective discharge formation and the generation of shock waves used in technological processes of material destruction, treatment, and purification. Experimental data are presented, and the prospects for applying the obtained results in engineering practice are discussed